Compreendendo a sexualidade na adolescência por meio do modelo biopsicossocial: estratégias didáticas para o professor do ensino médio - Assis, Thiago Brandão de (2024)
The issue of sexuality is an inherent aspect of human life, encompassing bodily, subjective, and emotional sensations that extend beyond reproduction. In biology, there are two ways of perceiving/teaching about sexuality: the biological-centered and preventive model, which emphasizes biological aspects of sexuality, and the biopsychosocial model, which presents broader conceptions of sexuality. The second model was emphasized, as sexuality is understood as a natural phenomenon expressed in multiple ways, at different stages of life, in various contexts, and subjective, social, and cultural realities. Inquiry-based teaching plays a crucial role in sex education, enabling students to explore STI prevention, contraception, sexual health, and relationships to promote critical skills, informed decision-making, and understanding of the complexities of human sexuality, contributing to a more open, inclusive, and contextualized education. The aim was to develop the theme of sex education through group dynamics workshops that promote an investigative approach, allowing students to explore concepts, social norms, and gender issues through research, discussion, and critical analysis, enabling them to make informed decisions and promoting a comprehensive understanding of sexuality. The project was carried out at ECIT Cristiano Cartaxo, located in the city of Cajazeiras/PB, with three secondary school classes, totaling 18 students aged between 16 and 18. The work presented an applied nature, a quantitative-qualitative approach of the participatory research type. The methodological strategies included a meeting with parents/guardians, the administration of a diagnostic survey, and active methodologies based on group dynamics workshops. The work began with an initial understanding of what the students knew about sexuality and sex education through the application of a diagnostic survey, and from this point, the implementation of the activities began with the construction of a coexistence contract and the dynamics focusing on the biopsychosocial aspect. Quantitative and qualitative data were collected from the diagnostic survey and through the recording of images, audios, videos, and texts. The information from the questions was tabulated in spreadsheets to be analyzed in terms of the participants' responses to the collection instrument. The participants' speeches were categorized and analyzed from the perspective of Bardin's content analysis. Through the group dynamics workshops, the participants realized the complexity of adolescence, as it is a unique period for each individual. In addition, the biopsychosocial approach brought a new dimension of learning in which the students correlated biological aspects with social, economic, cultural, and psychological aspects. The culmination was the result of debates during the group dynamics workshops involving work done by the students themselves on the themes of STIs and contraception, myths and truths, and female empowerment. The activities carried out were compiled into a digital booklet, which will help high school teachers to work on the subject of sex education using active methodologies, emphasizing the role of the student as the protagonist of learning.